Transcending traditional paradigms: the multifaceted realm of phenomenon-based learning - Surattana Adipat (Frontiers in Education, 2024)
Phenomenon-based learning emphasizes direct engagement with everyday phenomena, highlighting how personal experiences influence our understanding of reality. This pedagogical approach promotes an educational model centered on students’ real-life experiences. Renowned for its educational standards, Finland has embraced this methodology. Through significant shifts, the nation has pursued an interdisciplinary education that values diverse perspectives. Despite challenges, notably resistance from educators, Finland’s innovative strategies and commitment to high-quality education have been pivotal to its success. This transformation in teaching methodology diverges from traditional methods, endorsing a comprehensive skillset, innovation, and practical problem-solving. The adoption of this approach by various countries attests to its efficacy in fostering essential academic competencies. This article seeks to elucidate the fundamental concepts of phenomenon-based learning, dissect its five stages and their impact on competency development, examine its theoretical grounding and relationship to the approach, highlight the target competencies, and discuss the method’s implementation in education.